PENGARUH PENGGUNAAN LAHAN PERTANIAN TERHADAP KETAHANAN PANGAN DI KABUPATEN MINAHASA UTARA - Nova S. Larenggam; Esry O.H. Laoh; Ellen G. Tangkere; Oktavianus Porajouw (COCOS, 2015)
ABSTRACTThis study aims to determine the effect of the use of agricultural land to food security. This study was conducted in North Minahasa Regency, and the data used was collected from various government agencies in North Minahasa Regency, including the Food Security Agency, Agriculture and Livestock Office, and Building Permits Office. The data was then analyzed descriptively. The results showed that the use of agricultural land in North Minahasa decreased due to the increase in non-agricultural use, and could affect the food security. However, the current food security in North Minahasa was still in positive trend because due to the increase in productivity and the effect of growing season change.